Analysis of circulating respiratory syncytial virus A strains in Shanghai, China identified a new and increasingly prevalent lineage within the dominant ON1 genotype - Zhao, Xue; Wang, Chun; Jiang, Hui; Zhang, Hong; Fang, Fanghao; Chen, Min; Yuan, Zhengan; Teng, Zheng; Liu, Jing; Zhang, Xi (Frontiers in Microbiology, 2022)
Respiratory syncytial virus A (RSV-A) is one of the commonest pathogens causing acute respiratory tract infections in infants and children globally. The currently dominant circulating genotype of RSV-A, ON1, was first detected in Shanghai, China in 2011, but little data is available regarding its subsequent circulation and clinical impact here. In this work, we analyzed RSV-A infection in a cohort of patients hospitalized for acute respiratory infections in Shanghai Children’s Hospital, and RSV-A was detected in ~10% of these cases. RSV-A G gene sequencing revealed that all successfully sequenced strains belonged to ON1 genotype, but in phylogenetic analysis, the majority of these sequences formed a clade separate from the four previously established lineages within ON1. The new lineage, denoted ON1-5, was supported by phylogenetic analyses using additional G gene sequences from RSV-A strains isolated in Shanghai and elsewhere. ON1-5 first appeared in 2015 in China and the Netherlands, and has since spread to multiple continents and gained dominance in Asia. In our cohort, ON1-5 was not associated with markedly different clinical presentations compared to other ON1 lineages. ON1-5 strains are characterized by 4 amino acid variations in the 2 mucin-like regions of G protein, and one variation (N178G) within the highly conserved CCD domain that is involved in receptor binding. These data highlight the continuous evolution of RSV-A, and suggest the possibility of the virus acquiring variations in domains traditionally considered to be conserved for fitness gain.